Pengaruh CAR, FDR, BOPO dan PDRB terhadap Non-Performing Financing pada Bank Umum Syariah BUMD di Indonesia - Nurfadhila Tsania; Destian Arshad Darulmalshah Tamara; Setiawan Setiawan (Journal of Applied Islamic Economics and Finance, 2022)
The purpose of this study was to determine the influence of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Operational Expenses on Operational Financing (BOPO) and Gross Regional Domestic Product (GRDP) partially on Non-Performing Financing (NPF) in Sharia Bank of Municipally-Owned Corporations in Indonesia The data analysis technique used is path analysis. This study selected a sample with a purposive sampling method and selected three Islamic Commercial Banks to be used. The data used is secondary data sourced from the financial reports of Islamic Commercial Banks and the Central Statistics Agency which have been published and collected using documentation techniques or direct quotations. The results of this study indicate that CAR, FDR, and GRDP have no effect on NPF meanwhile BOPO has an effect on NPF.